Pengaruh Time Management, Locus Of Control, Dan Phubbing Terhadap Prokrastinasi Akademik (Studi Kasus Generasi Z Di Jakarta) - Winarna, Ayu Dita; Rozamuri, Arif Murti (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
This research aims to determine the influence of Time Management, Locus of Control, and Phubbing on Academic Procrastination among Generation Z Students in Jakarta. The method used in this research is quantitative explanatory research. The data processing used is SPSS (Statistical Package for the Social Sciences) software version 25.0. The number of samples used was 100 respondents using a purposive sampling technique from Generation Z aged 18-24 years who were students in Jakarta. Data collection was carried out by distributing questionnaires online. The results of this research show that time management, locus of control, and phubbing significantly affect academic procrastination. Partially, time management has a significant negative effect on academic procrastination, locus of control has no significant effect on academic procrastination, and phubbing has a significant positive effect on academic procrastination.